Causes of maxillofacial patients mortality in a Nigerian tertiary hospital - Kelvin Uchenna Omeje; Ibiyinka Olushola Amole; Otasowie Daniel Osunde; Akinwale Adeyemi Efunkoya; Akinfenwa Taoheed Atanda (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
Background. An analysis of maxillofacial mortality was done in a Nigerian tertiary health care centre to determine the major causes of mortality and identify possible predisposing factors in our environment. Materials and methods. A retrospective analysis of mortality in maxillofacial surgery department of Aminu Kano Teaching Hospital from January 2005 to December 2014 was done. Data were analyzed using statistical package for social sciences (SPSS) version 15.0 (SPSS Inc, Chicago, IL). Results. A mortality rate of 1.8% (46 deaths from 2,540 admissions) was recorded. There were 35 males (76.1%) and 11 (23.9%) females. The mean age of the deceased patients was 40.0±13.0years. Orofacial infections (41.3%) and advanced (stage IV) orofacial malignancies (28.3%) accounted for most deaths. Conclusion. Fascial space infections and orofacial malignancies contribute largely to mortality in our setting. Late presentation was a major factor predisposing to mortality.